1994
DOI: 10.1177/140349489402200207
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of School Injuries in the Northern Part of Sweden

Abstract: The aim of this one-year investigation of school accidents is to obtain more knowledge for preventive work. In the age-group 7-19 years, 547 injuries were registered, mainly at three hospitals. The incidence rate was 25 per 1000 boys and 20 per 1000 girls per year. Most injuries occurred in intermediate and upper secondary school among boys and in upper school among girls. The relative risk of school injury compared with spare-time injury was 1.8 for boys and 2.6 for girls of compulsory school age. Most injuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 8 publications
0
17
0
3
Order By: Relevance
“…Hammarstrom et al [1] also found sporting activities to be the most frequent cause among 547 school accidents. The ratio of school sport accidents in the literature is between 33 and 41% [4,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hammarstrom et al [1] also found sporting activities to be the most frequent cause among 547 school accidents. The ratio of school sport accidents in the literature is between 33 and 41% [4,11].…”
Section: Discussionmentioning
confidence: 99%
“…The relative risk of a school accident compared to a nonschool-related accident is 1.8 for boys and 2.6 for girls [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As sports and physical activities have been promoted as part of health lifestyle, injury during these activities are a problem of public health [4][5][6][7][8]. Some studies have shown that the injury is associated with age, alcohol use, behavior, physical ability, health status, psychosomatic health complaints, sleep disorders, disabilities, and social conditions [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The injury is frequent in adolescents and they often result in heavy consequences (lesions, hospitalization, school absence, and care) [1][2][3][4]. As sports and physical activities have been promoted as part of health lifestyle, injury during these activities are a problem of public health [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%